Introduction : Arts integration and community engagement for intercultural dialogue through language education - Porto, Melina; Houghton, Stephanie Ann (2021)
Beyond description, the intensity and complexity of an individual human life deepens over time. Through academic engagement, the lives of teachers, students and researchers sometimes entwine in mutually enriching ways that result in multiple and ongoing personal and social transformations that propel them, and human society itself, forward in both seen and unseen ways that are sometimes beyond control or understanding. This special issue can be characterized as such. Through it, we put on the brakes, and relocate who we are, what we are doing, who we are becoming, and the respective role(s) we want to play in this world. Through compelling narrative, reflecting upon the many years of accumulating influences that have each led us to this resilient and durable point in time and space, we co-editors attempt to create objective, reasoned space through which to voice understandings gained about the complicated nature and relationship of language and the arts that have been culminating in our lives in, around and through our various joint collaboration(s).
Keywords: Community engagement; Intercultural communication and education; Intercultural dialogue; Language education; The arts